2023
DOI: 10.55519/jamc-01-10780
|View full text |Cite
|
Sign up to set email alerts
|

12 Month's Assessment of Clinical Efficacy of Resin Modified Glass Ionomer Cement and Flowable Composites in Restoration of Non-Carious Cervical Lesions, a Randomized Clinical Trial

Atikah Saghir,
Tehmina Rehman,
Bushra Irum
et al.

Abstract: Background: The objective of this study was to compare the clinical efficacy of Resin modified glass ionomer cement and Flowable composite in terms of retention, marginal adaptation and surface texture using United States Public Health Service criteria in non-carious cervical lesions measured over a period of one year. Methods: A Randomized Clinical Trial is conducted with Informed consent on 60 patients who are randomly allocated into 2 groups with at least 2 Non-Carious Cervical Lesions in each. Group 1 is u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…In total, 29 RCTs [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] were included, of which only 1 [ 50 ] was parallel. All studies reported that the total number of patients ranged from 10 to 92 and the number of teeth treated ranged from 16 to 180.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In total, 29 RCTs [ 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ] were included, of which only 1 [ 50 ] was parallel. All studies reported that the total number of patients ranged from 10 to 92 and the number of teeth treated ranged from 16 to 180.…”
Section: Resultsmentioning
confidence: 99%
“…The countries where the studies were carried out were: Brazil [ 49 , 59 , 60 , 61 , 63 , 66 ], Croatia [ 53 ], Egypt [ 44 , 47 ], Germany [ 50 , 70 , 71 ], India [ 45 , 56 , 57 ], Italy [ 53 ], Mexico [ 68 ], Nigeria [ 62 ], Pakistan [ 46 ], Romania [ 58 ], Serbia [ 53 ], Sweeden [ 55 ], Turkey [ 48 , 51 , 52 , 53 , 54 , 64 , 67 , 69 ], United Kingdom [ 65 ] and the United States [ 72 ]. Seven studies [ 44 , 47 , 48 , 50 , 53 , 54 , 56 ] mentioned that the evaluation criteria used for the analysis of the teeth were the FDI criteria.…”
Section: Resultsmentioning
confidence: 99%
“…It is well recognized that the etiology of NCCL is determined by a variety of variables, including the patient’s risk factor, which varies greatly, altering the therapeutic efficiency of restorative materials [ 48 ]. NCCLs are a common clinical manifestation with a complex etiology that increases with age.…”
Section: Discussionmentioning
confidence: 99%
“…Flowable Composite Group was 60% and RMGIC Group was 83%. The Chi-square test revealed a significant connection between retention and both groups [ 48 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several in vitro studies and clinical trials have proved the clinical efficacy of glass ionomers and resin-modified glass ionomers [6][7][8][9][10] . The main advantage of these materials is related to their fluoride releasing ability, which reduces the probability of developing new carious lesions adjacent to restorations (CAR) 11 .…”
Section: Introductionmentioning
confidence: 99%